First molecular screening of deafness in the Altai Republic population - Claustres Mireille; Osipova Ludmila; Tadinova Vera; Pallares-Ruiz Nathalie; Posukh Olga; Roux Anne-Françoise (BMC, 2005)
Abstract Background We studied the molecular basis of NSHL in Republic of Altai (South Siberia, Russia). The Altaians are the indigenous Asian population of the Altai Mountain region considered as a melting-pot and a dispersion center for world-wide human expansions in the past. Methods A total of 76 patients of Altaian, Russian or mixed ethnicity and 130 Altaian controls were analyzed by PCR-DHPLC and sequencing in the GJB2 gene. The GJB6 deletion and the common non-syndromic deafness-causing mitochondrial mutations were also tested when appropriate. Results 8.3% of the Altaian chromosomes were carrying GJB2 mutations versus 46.9% of the Russian chromosomes. The 235delC mutation was predominant among Altaians, whereas the 35delG mutation was most prevalent among Russian patients. Conclusion We found an Asian-specific GJB2 diversity among Altaians, and different GJB2 contribution for deafness in the Altaian and Russian patients. The high carrier frequency of 235delC in Altaians (4.6%) is probably defined by gene drift/founder effect in a particular group. The question whether the Altai region could be one of founder sources for the 235delC mutation widespread in Asia is open.